Model Project Based Learning Berbasis Tinkercad Untuk Meningkatkan Hasil Belajar Siswa Pada Materi Hukum Ohm - Kosegeran, Miguel Angle (Charm Sains: Jurnal Pendidikan Fisika, 2026)
This study aims to improve student learning outcomes using a Tinkercad-based project-based learning model on Ohm's Law material. The study was conducted at SMA Negeri 1 Tombatu, involving 50 grade XI students divided into experimental and control groups. The experimental class implemented PjBL assisted by Tinkercad, while the control class used conventional PjBL without digital media. This study used a quasi-experimental approach with a Randomized Control Group Pretest-Posttest design using two classes, each containing 25 students. The data collection instruments were learning outcome tests consisting of objective and essay questions given in the form of pre-tests and post-tests, as well as project assessment sheets. The data were analyzed using an independent sample t-test. The findings prove that the Tinkercad-based PjBL model effectively improves student learning outcomes, making it worthy of consideration as an innovative approach in physics learning, especially for mastering abstract concepts such as Ohm's Law.